Predictors of elevated carotid intima-media thickness as a surrogate marker for cardiovascular disease in pediatric chronic kidney disease. - Emi Yulianti; Retno Palupi-Baroto; Sasmito Nugroho; Noormanto Noormanto; Maria Grace Wilianto; Dwi Astuti Dharma Putri; Indah Kartika Murni (PLoS ONE)
Background Chronic kidney disease (CKD), especially in its late stages, carries significant morbidity and mortality, often due to cardiovascular problems. Mortality rates for children with CKD and cardiovascular disorders remain high even in high-income countries. Elevated carotid intima-media thickness (CIMT) is considered a marker for vascular thickness and future cardiovascular events in younger populations. This study aimed to determine predictors of cardiovascular events in pediatric patients with CKD with CIMT as a surrogate marker. Materials and methods A retrospective cohort study was conducted on children aged 2-18 years with CKD at Dr. Sardjito Hospital, Yogyakarta, Indonesia, from September 1st 2022-31st December 2023. We used multivariate logistic regression to identify independent predictors at diagnosis (e.g., age, male sex, obesity, CKD stage, and hypertension) associated with elevated CIMT (outcome), measured at least three months post-diagnosis as a proxy for cardiovascular risk. Results A total of 71 patients were recruited, 35 (49.3%) of whom were male, and the median age (range) was 14.67 years (4.6-18.8). Twenty-four children (33.8%) had increased vascular thickness. In the multivariate analysis, male sex was independently associated with increased vascular thickness with an adjusted odds ratio (95% CI) of 2.911 (1.012-8.371, p = 0.047). Conclusion Approximately one in three children with CKD experienced increased vascular thickness. Male was an independent predictor for increased vascular thickness in children with CKD.